2007
DOI: 10.1158/1078-0432.ccr-06-2340
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-Associated Antigen 9, a Novel Cancer Testis Antigen, Is a Potential Target for Immunotherapy in Epithelial Ovarian Cancer

Abstract: Purpose: Cancer testis antigens are a group of tumor antigens with gene expression restricted to male germ cells in the testis and in various cancerous tissues. Recently, we reported a novel testisspecific sperm-associated antigen 9 (SPAG9) gene, a new member of the c-Jun NH 2 -terminal kinase^interacting protein family, having functional role in sperm-egg fusion and mitogenactivated protein kinase signaling pathway. National Center for Biotechnology Information Blast searches revealed SPAG9 nucleotide sequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
77
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 24 publications
6
77
0
Order By: Relevance
“…10,11 We recently reported on the expression of a new member of the CT antigen family, sperm-associated antigen 9 (SPAG9), in patients with epithelial ovarian cancer (EOC). 13 We also demonstrated the presence of humoral immune response against SPAG9 in EOC patients. In addition, gene expression microarray analysis of cervix carcinoma cells 14 found the SPAG9 gene expressed along with other important much-studied genes.…”
mentioning
confidence: 51%
See 3 more Smart Citations
“…10,11 We recently reported on the expression of a new member of the CT antigen family, sperm-associated antigen 9 (SPAG9), in patients with epithelial ovarian cancer (EOC). 13 We also demonstrated the presence of humoral immune response against SPAG9 in EOC patients. In addition, gene expression microarray analysis of cervix carcinoma cells 14 found the SPAG9 gene expressed along with other important much-studied genes.…”
mentioning
confidence: 51%
“…17 SPAG9 protein expression in 4-lm paraffin-embedded sections (serial sections) of cervical cancer tissues was analyzed with anti-SPAG9 antibody or control immunoglobulin (Ig) G by immunohistochemistry as described earlier. 13 Paraffinembedded sections of ANCT were also processed as described earlier. 13 To confirm the grades of the cervical tumor, serial tumor sections were incubated with mouse monoclonal antiproliferating cell nuclear antigen (PCNA [F-2]; Santa Cruz Biotechnology, Calif) at a dilution of 1:50 at 4 C overnight in a humid chamber.…”
Section: In Situ Rna Hybridization and Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…8,9 Interestingly, none of these studies reported humoral response against CT antigens except OY-TES-1 which demonstrated that only 9.6% (7/73) patients generated auto-antibodies. 7 The most studied SPAG9 in various malignancies [20][21][22][23][24][25] was also shown to be associated with CRC in various stages and histotypes. 6 SPAG9 was also found to be highly immunogenic and demonstrated humoral response in CRC patients.…”
Section: Discussionmentioning
confidence: 97%